Low temperature properties of hot mix asphalts prepared with different polymer modified binders - Alatas, Taner; Yilmaz, Mesude (Croatian Soc Civil Engineers-Hsgi, 2017)
The low temperature crack propagation resistance of pure and polymer modified mixtures is analysed in the paper by means of linear and nonlinear fracture mechanics. The influence of two bitumen-modification binders is considered: styrene-butadienestyrene (SBS) and ethylene-vinyl-acetate (EVA). The experiments demonstrated that the fracture toughness values increase, and the maximum vertical strain values decrease, with a decrease in temperature. It was established by both techniques used in the paper that the lowest fracture toughness was obtained using the EVA binder.
Niskotemperaturna svojstva vru?ih asfaltnih mješavina s razli?itim polimerom modificiranim vezivima
Keywords: hot mix asphalt; low temperature performance; modification; fracture toughness